Atlas of material life : Northwestern Europe and East Asia, 15th to 19th Century - Vries, Peer; Vries, Annelieke (Leiden : Leiden University Press, 2020)
Large-scale comparative economic history of westernmost and easternmost Eurasia can be beneficial for the understanding of global history. This book provides a description of material life in North-western Europe and East Asia, for the period from the late fifteenth to the late nineteenth centuries, with a focus on developments in Great Britain and the Dutch Republic on the one hand and China and Japan on the other hand. With maps, tables, graphs and figures as a prominent and integral part of the book, it provides information, in an accessible format, on the main characteristics of the economic landscape of this period. It demonstrates the constraints to which all pre-industrial economies were subjected because of their dependence on organic natural resources but also the different ways in which the societies discussed dealt with those constraints. To provide a better understanding of this economy of limited possibilities, the final chapter of the book is devoted to the emergence of modern economic growth in Western Europe.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books; Material culture -- History -- East Asia; Material culture -- History -- Europe, Western